Negative electrode material of lithium ion battery, preparation method of negative electrode material and battery

By forming a uniform carbon layer on the surface of graphite, the surface defects and poor electrolyte compatibility of traditional graphite materials in lithium-ion batteries are solved, and the high capacity, low impedance and high head-effect performance of the negative electrode material are achieved.

CN119890264AActive Publication Date: 2025-04-25BTR NEW MATERIAL GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510045505.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-04-25
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Traditional graphite materials have many surface defects and poor electrolyte compatibility in lithium-ion batteries, resulting in serious irreversible side reactions in the material interface during charging and discharging, affecting the material's initial Coulomb efficiency and circulation capacity.

Method used

By forming a uniform carbon layer on the graphite surface, Raman spectroscopy and atomic force microscopy test ensure that the disorder of the carbon layer and the crystallization degree of graphite are within the appropriate range, thereby improving the lithium ion transport kinetics and interface transport performance.

Benefits of technology

The high capacity, low impedance, high magnification and high first-term efficiency performance of the negative electrode material are achieved, the electrolyte wetting ability and interface transmission dynamics are improved, and the cycle life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890264A_ABST
    Figure CN119890264A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material of a lithium ion battery, a preparation method of the negative electrode material and the battery. The negative electrode material comprises graphite and a carbon layer located on at least part of the surface of the graphite; the particle surface and the particle tangent plane of the negative electrode material are respectively tested by adopting a Raman spectrum, the ratio of the peak area of a characteristic peak D in the range of 1300 cm <-1 > to 1350 cm <-1 > to the peak area of a characteristic peak G in the range of 1500 cm <-1 > to 1580 cm <-1 > is ID / IG, the ID / IG ratio of the particle surface of the negative electrode material is A, the ID / IG ratio of the particle tangent plane of the negative electrode material is B, and 1.22 < A-B < = 2.10. The particle surface of the negative electrode material is tested through an atomic force microscope, a 1 [mu] m # imgabs0 # 1 [mu] m test area is randomly selected on the particle surface of the negative electrode material, the arithmetic mean value of the absolute value of the height deviation relative to the reference surface in the test area is S nm, and S is larger than or equal to 15 nm and smaller than or equal to 60 nm. The negative electrode material provided by the invention can comprehensively improve lithium ion transmission kinetics, first coulombic efficiency and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese patent application with application number 202411381906.2 and application name “A negative electrode material, preparation method thereof, and battery”. Technical Field

[0002] The present application relates to the technical field of negative electrode materials, and in particular, to a negative electrode material for a lithium-ion battery, a preparation method thereof, and a battery. Background Art

[0003] The rapid development of lithium-ion batteries has brought about rapid changes in human life. As one of the core components of lithium-ion batteries, negative electrode materials have a significant impact on the electrochemical performance of lithium-ion batteries. Therefore, the development of cost-effective negative electrode materials is of great significance in lithium-ion battery research. Graphite materials are widely used negative electrode materials for lithium-ion batteries, but traditional graphite materials still have many surface defects and poor electrolyte compatibility, which lead to serious irreversible side reactions at the material interface during charging and discharging, resulting in low initial Coulomb efficiency of the material and continuous decay of cycle capacity, which seriously hinders the further application of graphite negative electrode materials.

[0004] At present, the industry mainly uses surface coating to modify graphite to reduce direct contact between electrolyte and natural graphite and reduce the occurrence of side reactions. However, the surface and interface structure of graphite materials has a significant impact on performance such as capacity and lithium ion transmission dynamics. The existing coating processing technology cannot accurately control the interface characteristics of the graphite material surface and the internal particles, resulting in poor lithium ion transmission dynamics, low capacity, low initial efficiency and other problems. Summary of the invention

[0005] In view of this, the present application provides a negative electrode material for a lithium ion battery, a preparation method thereof, and a battery. The negative electrode material can comprehensively improve lithium ion transfer kinetics, first coulombic efficiency, and cycle performance.

[0006] In a first aspect, the present application provides a negative electrode material for a lithium ion battery, the negative electrode material comprising graphite and a carbon layer located on at least a portion of the surface of the graphite; Raman spectroscopy was used to test the particle surface and particle cross-section of the negative electrode material. -1 ~1350cm -1 The peak area of ​​the characteristic peak D in the range of 1500 cm -1 ~1580cm -1 The peak area ratio of the G characteristic peak within the range is I D / I G , the I on the surface of the particles of the negative electrode material is measured D / I G The ratio is A, the ID / I G The ratio is B, 1.22<AB≤2.10; The particle surface of the negative electrode material was tested by atomic force microscopy. A 1 μm particle was randomly selected from the particle surface of the negative electrode material. 1μm test area, the arithmetic mean of the absolute value of the height deviation relative to the reference surface in the test area is S nm, 15 nm≤S≤60 nm, where S= , n≥5, Z is the height deviation value of any test point in the test area relative to the reference surface.

[0007] In some embodiments, 1.70≤A≤3.00, 0.4≤B≤0.8.

[0008] In some embodiments, the graphite includes at least one of artificial graphite, natural graphite, and microcrystalline graphite.

[0009] In some embodiments, the fixed carbon content of the graphite is ≥ 95%.

[0010] In some embodiments, the carbon layer has a thickness of 15 nm to 250 nm.

[0011] In some embodiments, the carbon layer includes amorphous carbon.

[0012] In some embodiments, the median particle size of the negative electrode material is 4 μm to 25 μm.

[0013] In some embodiments, the specific surface area of ​​the negative electrode material is ≤6m 2 / g.

[0014] In some embodiments, the tap density of the negative electrode material is 0.75 g / cm 3 ~1.3g / cm 3 . In some embodiments, the oil absorption value of the negative electrode material is 38 mL / 100 g to 48 mL / 100 g.

[0015] The present application also provides a method for preparing a negative electrode material for a lithium ion battery, the method comprising the following steps: Dispersing a coating agent having an active group and a reaction regulator in an aqueous solution, and performing a prepolymerization reaction to obtain a prepolymerization solution, wherein the degree of polymerization of the polymer in the prepolymerization solution is 3 to 30; Adding graphite to the prepolymer solution for liquid phase coating, and performing solid-liquid separation to obtain a precursor, wherein the solid-liquid ratio of the graphite to the prepolymer solution is 1:(1.3-3.5), and the mass ratio of the graphite to the coating agent is 100:(4-30); The precursor is carbonized to obtain a negative electrode material.

[0016] In some embodiments, the active group includes at least one of a carbon-carbon double bond, a carboxyl group, a hydroxyl group, and an amine group.

[0017] In some embodiments, the reaction modifier includes at least one of a redox agent and a pH modifier.

[0018] In some embodiments, the reaction regulator includes a redox agent, and the mass ratio of the redox agent to the coating agent is 1:(0.7-2.0).

[0019] In some embodiments, the prepolymerization reaction time is controlled to be 1 h to 4 h.

[0020] In some embodiments, the liquid phase coating time is 4 hours to 24 hours.

[0021] In some embodiments, the capping agent having an active group includes at least one of styrene, fluorostyrene, bromostyrene, aminostyrene, styrenic acid, phenylpropionic acid, aniline, phenylenediamine, acrylic acid, methyl acrylate, ethyl acrylate, phenyl acrylate, benzyl acrylate, acrylamide, methacrylamide, ethylacrylamide, phenylacrylamide, maleic acid, maleic anhydride, maleic acid diamine, citric acid, mesaconic acid, itaconic acid, itaconic anhydride, sulfamic acid, ammonium sulfamic acid, benzoic acid, ammonium benzoate, and p-fluorobenzoic acid.

[0022] In some embodiments, the temperature of the carbonization treatment is 1000°C to 2300°C.

[0023] In some embodiments, the carbonization treatment is carried out for a holding time of 0.5 h to 6 h.

[0024] In some embodiments, the carbonization treatment is performed under a protective atmosphere. In a third aspect, the present application provides a battery, the battery comprising the above-mentioned negative electrode material or the negative electrode material prepared according to the above-mentioned preparation method.

[0025] The technical solution of this application has at least the following beneficial effects: The present application provides a negative electrode material for a lithium-ion battery, in which the Raman ratio A of the particle surface of the negative electrode material can be used to characterize the disorder of the carbon layer, and the Raman ratio B of the section of the negative electrode material particle can be used to characterize the crystallinity and quality of graphite. The inventors of the present application found in the research process that when AB is too small, the Raman ratios of the particle surface of the negative electrode material and the inside of the particle are too close, indicating that the Raman ratio A of the carbon layer is too small or the Raman ratio B of the section of the negative electrode material is too high, the disorder of the carbon layer is insufficient or the crystallinity of the graphite is insufficient, which will cause the negative electrode material to have poor rate performance and low capacity. When AB is too large, the difference between the Raman ratios of the particle surface and the inside of the particle of the negative electrode material is too large, the dynamic transmission performance of the connection interface between the graphite and the carbon layer is greatly different, the impedance of the negative electrode material increases, and the rate performance of the negative electrode material deteriorates.

[0026] In addition, the inventors of this application found that the microstructure of the surface of the negative electrode material particles is closely related to the material capacity, first effect and other properties during the research process. The arithmetic mean of the absolute value of the height deviation measured relative to the reference plane in the scanning area using an atomic force microscope test is S nm. When the negative electrode material satisfies 15≤S≤60, the negative electrode material has the characteristics of high capacity, high first effect and low interface impedance. The inventors found that when S is controlled in the range of 15nm~60nm, the surface coating of the negative electrode material is evenly distributed on the surface of the graphite particles, and the roughness of the coating layer is also in the appropriate range, which is conducive to electrolyte infiltration and interface impedance reduction. When S <15nm, the surface of the negative electrode material is too flat and smooth, which is not conducive to electrolyte infiltration, resulting in a decrease in the capacity of the negative electrode material; when S>60nm, the surface roughness of the negative electrode material is too high, and the electrolyte wettability is enhanced, but due to the decrease in the uniformity of the coating layer on the surface of the negative electrode material, the interface side reactions of the negative electrode material increase, and the irreversible consumption of active lithium ions increases, which reduces the first effect of the negative electrode material.

[0027] The present application controls AB and S within the above range, so that the difference in Raman ratio between the surface and the interior of the negative electrode material particles and the flatness of the surface coating layer can be within an appropriate range, which can ensure the regularity of the internal graphite structure and the high disorder of the external coating layer structure, and can also ensure the uniform distribution and appropriate morphological flatness of the graphite surface coating layer. Therefore, the negative electrode material provided by this patent can effectively improve the electrolyte wettability and improve the interface transmission dynamics of the negative electrode material, so that the negative electrode material has the excellent performance of high capacity, low impedance, high rate and high initial efficiency.

[0028] The present application provides a preparation method for a lithium-ion battery, wherein a coating agent having an active group is prepolymerized, and the degree of polymerization of the polymer molecules in the obtained prepolymer solution is in the range of 3 to 30, and the polymer is mainly an oligomer with a small molecular chain, which can be evenly dispersed in the prepolymer solution. Then, graphite is added to the prepolymer solution for liquid phase coating. During the coating process, the polymer evenly dispersed in the prepolymer solution can be deposited and attached to the surface of the graphite particles to form a uniform polymer coating layer; at the same time, the solid-liquid ratio of graphite to the prepolymer solution is controlled to be 1: (1.3 to 3.5), so that the thickness of the polymer coating layer evenly attached to the graphite surface is within a suitable range, and while increasing the capacity of the negative electrode material, the lithium ion interface transmission efficiency of the negative electrode material is increased. Finally, through carbonization treatment, the polymer coating layer can be fully carbonized to form a carbon layer, the carbon material in the carbon layer has a high degree of disorder, and the difference in the Raman ratio between the surface of the negative electrode material particle and the inside of the particle can also be within a suitable range. In addition, the flatness of the material surface coating layer can also be within a suitable range. The above preparation method not only ensures the regularity of the graphite structure inside the negative electrode material particles, the connection interface between the graphite and the carbon layer can also have better transmission power, but also improves the wettability of the contact interface between the surface of the negative electrode material and the electrolyte. The negative electrode material prepared by the preparation method of the present application can have excellent lithium ion transmission power performance, capacity, first coulomb efficiency and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A process flow chart of the preparation method of the negative electrode material provided in this application; Figure 2 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application; Figure 3a and Figure 3b They are electron microscope images of the negative electrode material prepared in Example 1 of the present application at different magnifications; Figure 3c This is an electron microscope image of a cross section of the negative electrode material prepared in Example 1 of the present application; Figure 4a The Raman test spectrum of the material particles prepared in Example 1 of the present application is: Figure 4b A Raman test spectrum of a cross section of the material prepared in Example 1 of the present application; Figure 5 This is an atomic force microscope image of the surface of the material prepared in Example 1 of the present application; Figure 6 This is a comparison chart of the electrochemical impedance of the negative electrode materials prepared in Example 1 of the present application and Comparative Example 4. DETAILED DESCRIPTION

[0030] In order to better illustrate the present application and facilitate understanding of the technical solution of the present application, the present application is further described in detail below. However, the following embodiments are only simple examples of the present application and do not represent or limit the scope of protection of the present application. The scope of protection of the present application shall be subject to the claims.

[0031] Based on this, in a first aspect, the present application provides a negative electrode material, the negative electrode material comprising graphite and a carbon layer located on at least a portion of the surface of the graphite; Raman spectroscopy was used to test the particle surface and particle cross-section of the negative electrode material. -1 ~1350cm -1 The peak area of ​​the characteristic peak D in the range of 1500 cm -1 ~1580cm -1 The peak area ratio of the G characteristic peak within the range is I D / I G , the I on the surface of the particles of the negative electrode material is measured D / I G The ratio is A, the I D / I G The ratio is B, 1.22<AB≤2.10; The particle surface of the negative electrode material was tested by atomic force microscopy. A 1 μm particle was randomly selected from the particle surface of the negative electrode material. 1μm test area, the arithmetic mean of the absolute value of the height deviation relative to the reference surface in the test area is S nm, 15nm≤S≤60nm, where S= , n≥5, Z is the height deviation value of any test point in the test area relative to the reference plane. In the negative electrode material provided in the present application, the Raman ratio A of the particle surface of the negative electrode material can be used to characterize the disorder degree of the carbon layer, and the Raman ratio B of the section of the negative electrode material particle can be used to characterize the degree of crystallization and quality of graphite. The inventors of the present application found in the research process that when AB is too small, the Raman ratios of the particle surface of the negative electrode material and the inside of the particle are too close, indicating that the Raman ratio A of the carbon layer is too small or the Raman ratio B of the section of the negative electrode material is too high, the disorder degree of the carbon layer is insufficient or the crystallization degree of the graphite is insufficient, which will cause the negative electrode material to have poor rate performance and low capacity. When AB is too large, the difference between the Raman ratios of the particle surface and the inside of the particle of the negative electrode material is too large, the kinetic transmission performance of the connection interface between graphite and the carbon layer is greatly different, the impedance of the negative electrode material increases, and the rate performance of the negative electrode material deteriorates.

[0032] In addition, the inventors of this application found during the research process that the surface of the material particles is closely related to the material capacity, first effect and other properties. The arithmetic mean of the absolute value of the height deviation measured relative to the reference plane in the scanning area using an atomic force microscope test is S nm, and S can specifically be 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm or 60nm, etc., of course, it can also be other values ​​within the above range, which are not limited here. When the negative electrode material satisfies 15nm≤S≤60nm, the negative electrode material has the characteristics of high capacity, high first efficiency and low interface impedance. The inventors have found that when S is controlled in the range of 15nm~60nm, the surface coating of the negative electrode material is evenly distributed on the surface of the graphite particles, and the roughness of the coating is also in a suitable range, which is conducive to electrolyte infiltration and interface impedance reduction. When S is less than 15nm, the surface of the negative electrode material is very flat and smooth, which is not conducive to electrolyte infiltration, resulting in a decrease in the capacity of the negative electrode material; when S is greater than 60nm, the surface roughness of the negative electrode material is too high, and the electrolyte wettability is enhanced, but due to the decrease in the uniformity of the coating layer on the surface of the negative electrode material, the interface side reactions of the negative electrode material increase, and the irreversible consumption of active lithium ions increases, which reduces the first efficiency of the negative electrode material. The present application controls AB and S within the above range, so that the difference in Raman ratio between the surface of the negative electrode material particles and the interior of the particles and the flatness of the surface coating layer are within a suitable range, which can ensure the regularity of the internal graphite structure and the high disorder of the external coating layer structure, and ensure the uniform distribution and morphological flatness of the graphite surface coating layer. The former helps to improve the rate performance and capacity of the negative electrode material, and the latter helps to improve the first efficiency and capacity of the negative electrode material. Therefore, the negative electrode material provided by this patent can effectively improve the electrolyte wettability, improve the interface transmission dynamics of the negative electrode material, and enable the negative electrode material to have high capacity, low impedance, high rate and high first efficiency performance.

[0033] In some embodiments, 1.70≤A≤3.00, specifically 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.5, 2.8 or 3.0, etc., and of course other values ​​within the above range, which are not limited here. In the present application, the A value is controlled within the above range, the carbon layer has a high degree of structural disorder, which can improve the wettability of the contact interface between the surface of the negative electrode material and the electrolyte, reduce the occurrence of interfacial side reactions of the negative electrode material, reduce the consumption of irreversible active lithium ions, improve the lithium ion transmission power, reduce the interface impedance of the contact interface, and improve the first coulombic efficiency and electrochemical performance of the negative electrode material.

[0034] In some embodiments, 0.4≤B≤0.8, specifically 0.4, 0.5, 0.55, 0.58, 0.6, 0.7, 0.75 or 0.8, etc., and of course other values ​​within the above range, which are not limited here. In the present application, the B value is controlled within the above range, the graphitization degree of graphite is appropriate, the structural regularity of graphite is good, and the interface impedance of the connection interface between graphite and carbon layer can be controlled within a suitable range, which is conducive to improving the capacity and the first coulombic efficiency of the negative electrode material.

[0035] In some embodiments, the specific value of AB may be 1.26, 1.3, 1.5, 1.6, 1.8, 1.9, 2.0, 2.05 or 2.1, etc. Of course, it may also be other values ​​within the above range, which is not limited here.

[0036] In some embodiments, the graphite includes at least one of artificial graphite, natural graphite and microcrystalline graphite. Natural graphite is flake graphite, which is natural phaneritic graphite. It is shaped like fish phosphate, belongs to the hexagonal system, has a layered structure, and has good properties such as high temperature resistance, electrical conductivity, thermal conductivity, lubrication, plasticity, and acid and alkali resistance. Artificial graphite is a graphite material obtained by carbonizing organic matter and then subjecting it to high-temperature graphitization treatment.

[0037] In some embodiments, the graphite includes spherical graphite, and the spherical graphite is natural graphite.

[0038] In some embodiments, the mass content of carbon in the graphite is ≥ 95%, specifically 95%, 96%, 97%, 97.5%, 98.3%, 98.8% or 99%, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. Preferably, the mass content of carbon in the graphite is ≥ 99%.

[0039] In some embodiments, the thickness of the carbon layer is 15 nm to 250 nm, specifically 15 nm, 20 nm, 30 nm, 40 nm, 50 nm, 80 nm, 100 nm, 150 nm, 200 nm, 220 nm or 250 nm, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. Controlling the thickness of the carbon layer within the above range is conducive to improving the lithium ion transmission power of the negative electrode material, reducing the occurrence of side reactions between the negative electrode material and the electrolyte, and improving the first coulomb efficiency.

[0040] In some embodiments, the carbon layer includes amorphous carbon and graphitized carbon, and the carbon layer has good compatibility with the electrolyte, thereby ensuring the stability of the electrical performance of the negative electrode material during the charge and discharge process.

[0041] In some embodiments, the specific surface area of ​​the negative electrode material is ≤6m 2 / g; specifically, it can be 1.0m2 / g, 1.8m 2 / g, 2.6m 2 / g, 3.5m 2 / g, 5.0m 2 / g or 6.0m 2 / g, and of course, it can be other numbers within the above range, which is not limited here. Controlling the specific surface area of ​​the negative electrode material within the above range is beneficial to improving the cycle performance of the battery made of the negative electrode material.

[0042] In some embodiments, the median particle size of the negative electrode material is 4 μm to 25 μm; more specifically, it can be 4 μm, 6 μm, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, 15 μm, 17 μm, 20 μm, 22 μm or 25 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] In some embodiments, the tap density of the negative electrode material is 0.75 g / cm 3 ~1.3g / cm 3 ; Specifically, it can be 0.75g / cm 3 , 0.8g / cm 3 , 0.85g / cm 3 , 0.9g / cm 3 , 0.92g / cm 3 , 1.0g / cm 3 , 1.05g / cm 3 , 1.1g / cm 3 , 1.15g / cm 3 , 1.2g / cm 3 , 1.25g / cm 3 or 1.3 g / cm 3 , of course, it can also be other numbers within the above range, which is not limited here. In the present application, the tap density of the negative electrode material is controlled within the above range, which is conducive to improving the energy density of the lithium ion battery made of the negative electrode material.

[0044] In some embodiments, the oil absorption value of the negative electrode material is 38 mL / 100g to 48 mL / 100g, specifically 38 mL / 100g, 39 mL / 100g, 40 mL / 100g, 41 mL / 100g, 42 mL / 100g, 43 mL / 100g, 44 mL / 100g, 45 mL / 100g or 48 mL / 100g, etc., and of course, it can also be other values ​​within the above range, which is not limited here. The negative electrode material of the present application, due to the high degree of structural disorder of the carbon layer, the oil absorption value of the negative electrode material can be controlled within the above range, which can improve the wettability of the contact interface between the surface of the negative electrode material and the electrolyte, enhance the lithium ion transmission power, and reduce the interface impedance of the contact interface.

[0045] In a second aspect, the present application provides a method for preparing a negative electrode material, such as Figure 1 As shown, the following steps are included: Step S10, dispersing a capping agent having an active group and a reaction regulator in an aqueous solution, and performing a prepolymerization reaction to obtain a prepolymerization solution, wherein the degree of polymerization of the polymer in the prepolymerization solution is 3-30.

[0046] Step S20, adding graphite to the prepolymer solution for liquid phase coating, and performing solid-liquid separation to obtain a precursor, wherein the solid-liquid ratio of graphite to the prepolymer solution is 1:(1.3-3.5), and the mass ratio of graphite to the coating agent is 100:(4-30).

[0047] Step S30, carbonizing the precursor to obtain a negative electrode material.

[0048] In the present application, the degree of polymerization of the polymer molecules in the obtained prepolymer solution is within the range of 3-30 by prepolymerizing the coating agent with active groups, and the polymer is mainly an oligomer with a small molecular chain, which can be evenly dispersed in the prepolymer solution. Then, graphite is added to the prepolymer solution for liquid phase coating. During the coating process, the polymer evenly dispersed in the prepolymer solution can be deposited and attached to the surface of the graphite particles to form a uniform polymer coating layer; at the same time, the solid-liquid ratio of graphite to the prepolymer solution is controlled to be 1: (1.3-3.5), so that the thickness of the polymer coating layer evenly attached to the graphite surface is within a suitable range, while improving the capacity of the negative electrode material, the lithium ion interface transmission efficiency of the negative electrode material is improved. Finally, through carbonization treatment, the polymer coating layer can be fully carbonized to form a carbon layer, the carbon material in the carbon layer has a high degree of disorder, and the difference in the Raman ratio between the surface of the negative electrode material particle and the inside of the particle can also be within a suitable range. In addition, the flatness of the material surface coating layer can also be within a suitable range. The above preparation method not only ensures the regularity of the graphite structure inside the negative electrode material particles, the connection interface between the graphite and the carbon layer can also have better transmission power, but also improves the wettability of the contact interface between the surface of the negative electrode material and the electrolyte. The negative electrode material prepared by the preparation method of the present application can have excellent lithium ion transmission power performance, capacity, first coulomb efficiency and cycle performance.

[0049] The following is a detailed description of the preparation method provided in this scheme: Step S10, dispersing a capping agent having an active group and a reaction regulator in an aqueous solution, and performing a prepolymerization reaction to obtain a prepolymerization solution, wherein the degree of polymerization of the polymer in the prepolymerization solution is 3-30.

[0050] In some embodiments, the degree of polymerization of the polymer in the prepolymer solution is in the range of 3-30, and may be 3, 5, 10, 15, 20, 25 or 30, etc. When the degree of polymerization of the prepolymer molecules is low, the utilization rate of the coating agent is reduced, and the free coating agent that is not polymerized and deposited in the solid-liquid separation stage is directly wasted, and the production cost increases; when the degree of polymerization of the prepolymer molecules is high, the disorder of the final coating agent polymer deposition layer is reduced, so that the Raman value of the final negative electrode material is reduced, which is not conducive to the improvement of the kinetic performance.

[0051] In some embodiments, the active group includes at least one of a carbon-carbon double bond, a carboxyl group, a hydroxyl group, and an amine group.

[0052] In some embodiments, the capping agent having an active group includes at least one of styrene, fluorostyrene, bromostyrene, aminostyrene, styrenic acid, phenylpropionic acid, aniline, phenylenediamine, acrylic acid, methyl acrylate, ethyl acrylate, phenyl acrylate, benzyl acrylate, acrylamide, methacrylamide, ethylacrylamide, phenylacrylamide, maleic acid, maleic anhydride, maleic acid diamine, citric acid, mesaconic acid, itaconic acid, itaconic anhydride, sulfamic acid, ammonium sulfamic acid, benzoic acid, ammonium benzoate, and p-fluorobenzoic acid.

[0053] In some embodiments, the reaction modifier includes at least one of a redox agent and a pH modifier.

[0054] In some embodiments, the redox agent includes at least one of azobisisobutyronitrile, azobisisoheptylnitrile, hydrogen peroxide, ammonium persulfate, sodium persulfate, potassium persulfate, aluminum chloride, and ferric chloride.

[0055] In some embodiments, the pH adjuster includes at least one of sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate, hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, and acetic acid.

[0056] In some embodiments, the coating agent includes a coating agent having an amine group, which may be at least one of aminostyrene, aniline, phenylenediamine, acrylamide, methacrylamide, ethylacrylamide, phenylacrylamide, maleic acid diamine, aminosulfonic acid, ammonium aminosulfonate, and ammonium benzoate.

[0057] In some embodiments, the coating agent includes a coating agent having an amine group, the reaction regulator includes a pH regulator, and the pH regulator includes at least one of sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate, hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, and acetic acid.

[0058] In some embodiments, the pH value of the prepolymerization reaction is controlled at 4 to 7, specifically 4, 4.5, 5, 5.5, 6, 6.5 or 7, etc., and of course other values ​​within the above range, which are not limited here. When the pH value of the prepolymerization reaction is high, it will affect the prepolymerization degree of the coating agent, resulting in a low degree of disorder in the polymer deposition layer deposited on the graphite surface, which ultimately affects the A value of the negative electrode material. When the pH value of the prepolymerization reaction is low, the prepolymerization reaction is insufficient, most of the coating agent is still free in the solution, and the polymer deposition layer deposited on the graphite surface is insufficient.

[0059] In some embodiments, the coating agent includes a coating agent having an amine group, and the reaction regulator further includes a redox agent, and the redox agent includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile, hydrogen peroxide, ammonium persulfate, sodium persulfate, potassium persulfate, aluminum chloride, and ferric chloride. The addition of the redox agent can promote the prepolymerization reaction of the coating agent containing the active group.

[0060] In some embodiments, the coating agent includes a coating agent having a carbon-carbon double bond, which can be acrylic acid, methyl acrylate, ethyl acrylate, phenyl acrylate, benzyl acrylate, etc. The temperature of the prepolymerization reaction is 40°C to 70°C, which can be 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C, etc. Of course, it can also be other values ​​within the above range, which is not limited here. The present application controls the temperature of the prepolymerization reaction within the above range so that the coating agent can be fully prepolymerized. When the temperature of the prepolymerization reaction is too high, the prepolymerization degree of the coating agent is too high, resulting in an uneven polymer coating layer on the graphite surface; when the temperature of the prepolymerization reaction is too low, the prepolymerization degree of the coating agent is too low, and it is difficult for the oligomer to be uniformly deposited and attached to the graphite surface, resulting in a waste of the coating agent.

[0061] In some embodiments, the mass ratio of the redox agent to the coating agent is 1:(0.7-2.0), specifically 1:0.7, 1:0.9, 1:1.0, 1:1.1, 1:1.2, 1:1.5, 1:1.7, 1:1.9 or 1:2.0, etc. Of course, it can also be other values ​​within the above range, which are not limited here. If the amount of redox agent added is too low, it will affect the prepolymerization degree of the coating agent, resulting in a low degree of disorder in the polymer deposition layer deposited on the graphite surface, which ultimately affects the A value of the carbon layer of the negative electrode material. When the amount of redox agent added is too high, the coating agent polymerizes too quickly, resulting in the coating agent being unable to be evenly distributed on the graphite surface, and too much redox agent will also increase production costs.

[0062] In some embodiments, the prepolymerization reaction time is controlled to be 1 h to 4 h, specifically 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h or 4 h, etc., and of course other values ​​within the above range are not limited here. If the prepolymerization reaction time is too short, the content of prepolymerized polymer molecules in the prepolymerization solution is low, and the prepolymerization reaction is insufficient. If the prepolymerization reaction time is too long, the production efficiency is reduced, which is not conducive to industrial preparation.

[0063] Step S20, adding graphite to the prepolymer solution for liquid phase coating, and performing solid-liquid separation to obtain a precursor, wherein the solid-liquid ratio of the graphite to the prepolymer solution is 1: (1.3-3.5), and the mass ratio of the graphite to the coating agent is 100: (4-30).

[0064] In some embodiments, the graphite includes at least one of artificial graphite and natural graphite. Natural graphite is flake graphite or spherical graphite obtained by shaping flake graphite, which is natural phaneritic graphite, shaped like fish phosphate, belonging to the hexagonal system, and presenting a layered structure, and has good properties such as high temperature resistance, electrical conductivity, thermal conductivity, lubrication, plasticity, and acid and alkali resistance. Artificial graphite is a graphite material obtained by carbonizing organic matter and then subjecting it to high-temperature graphitization treatment.

[0065] In some embodiments, the graphite includes spherical graphite, and the spherical graphite is natural graphite.

[0066] In some embodiments, the median particle size of the graphite is 1 μm to 30 μm, more specifically, it can be 1 μm, 5 μm, 8 μm, 10 μm, 11 μm, 13 μm, 16 μm, 18 μm, 20 μm, 23 μm, 26 μm or 30 μm, etc., but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. After many experiments, it was found that the median particle size of graphite was controlled within the above range, which is beneficial to reduce the specific surface area of ​​graphite, reduce the contact between graphite and electrolyte, and inhibit the occurrence of side reactions. Preferably, the median particle size of graphite is 5 μm to 20 μm.

[0067] In some embodiments, the mass content of carbon in the graphite is ≥ 95%, specifically 95%, 96%, 97%, 97.5%, 98.3%, 98.8% or 99%, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. Preferably, the mass content of carbon in the graphite is ≥ 99%.

[0068] In some embodiments, the solid-liquid ratio of graphite to the prepolymer solution is 1: (1.3-3.5) g / mL, which can be specifically 1: 1.3 g / mL, 1: 1.5 g / mL, 1: 1.8 g / mL, 1: 1.9 g / mL, 1: 2.0 g / mL, 1: 2.5 g / mL, 1: 3.0 g / mL, 1: 3.5 g / mL, etc., but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. In the present application, the solid-liquid ratio of graphite to the prepolymer solution is controlled within the above range, so that the concentration of polymer molecules in the prepolymer solution per unit volume can be controlled, so that the thickness of the polymer coating layer uniformly attached to the graphite surface is within a suitable range, while improving the capacity of the negative electrode material, the lithium ion interface transmission efficiency of the negative electrode material is improved. When the solid-liquid ratio is too large, too much graphite is added, and the polymer in the prepolymer solution is insufficient, so it is difficult to ensure that a polymer coating layer of uniform thickness is formed on the surface of the graphite particles, and the interface transmission of the negative electrode material is hindered, which affects the capacity of the negative electrode material. When the solid-liquid ratio is too small, the amount of graphite added is too little, the polymer coating layer on the surface of the graphite particles is too thick, and the capacity of the negative electrode material decreases.

[0069] In some embodiments, the mass ratio of graphite to coating agent is 100: (4-30), specifically 100: 4, 100: 5, 100: 8, 100: 10, 100: 15, 100: 20, 100: 25 or 100: 30, etc., and of course, it can be other values ​​within the above range, which are not limited here. When the amount of coating agent added is too little, it is difficult to deposit a uniform polymer coating layer on the graphite surface. When the amount of coating agent added is too much, the thickness of the polymer coating layer deposited on the graphite surface is too large, resulting in the interface transmission of the negative electrode material being blocked, affecting the capacity of the negative electrode material.

[0070] In some embodiments, the liquid phase coating time is 4 hours to 24 hours, specifically 4 hours, 5 hours, 8 hours, 10 hours, 15 hours, 18 hours, 20 hours, 23 hours, 24 hours, etc. When the liquid phase coating time is insufficient, it is difficult for the polymer molecules in the prepolymer solution to fully deposit and adhere to the surface of the graphite particles, and the coating layer on the graphite surface is unevenly distributed; when the liquid phase coating time is too long, the production efficiency is reduced, which is not conducive to industrial preparation.

[0071] In some embodiments, the liquid phase coating is performed under stirring, and the polymer formed by polymerization of the coating agent having active groups is deposited and attached to the surface of the graphite.

[0072] The present application controls the solid-liquid ratio, time and amount of coating agent added during liquid phase coating, and can promote the polymer formed by the coating agent having active groups to be uniformly deposited and attached to the surface of the graphite under stirring.

[0073] In some embodiments, after the liquid phase is coated, the mixed liquid is subjected to solid-liquid separation to obtain a solid which is then dried to obtain a precursor.

[0074] In some embodiments, the solid-liquid separation includes at least one of suction filtration, centrifugation and natural volatilization.

[0075] In some embodiments, the drying process comprises at least one of air drying, vacuum drying, freeze drying and spray drying.

[0076] S30, carbonizing the precursor to obtain a negative electrode material.

[0077] In some embodiments, the temperature of the carbonization treatment is 1000°C to 2300°C, specifically, it can be 1000°C, 1300°C, 1500°C, 1800°C, 1900°C, 2000°C, 2200°C, 2300°C, etc., but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. When the temperature of the carbonization treatment is low, the Raman value of the carbon layer of the negative electrode material is high, that is, the disorder of the carbon layer is high, resulting in aggravated interface side reactions and reduced first efficiency of the negative electrode material; when the temperature of the carbonization treatment is too high, the Raman value of the carbon layer of the negative electrode material is low, that is, the disorder of the carbon layer is low, resulting in poor interface transmission dynamics.

[0078] In some embodiments, the holding time of the carbonization treatment is 0.5h~6h, specifically, it can be 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0079] In some embodiments, the carbonization treatment is performed under a protective atmosphere, and the protective atmosphere includes at least one of nitrogen, helium, neon, argon, krypton and xenon.

[0080] The embodiment of the present invention further provides a battery, Figure 2 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 2 As shown, the battery includes a housing and an electrode assembly, and the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2. In other embodiments, the electrode assembly can also be a winding structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence and then winding them.

[0081] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 101 and a positive electrode active layer 102 disposed on at least one surface of the positive electrode current collector 101 .

[0082] In some embodiments, the positive electrode current collector 101 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active layer 102 includes a positive electrode active material, which includes a compound that can reversibly embed and de-embed metal ions.

[0083] In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide, a sodium transition metal composite oxide, etc. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese, and nickel.

[0084] In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O 4) 、LiNi 0.5 Mn 1.5 O4) or at least one of lithium iron phosphate (LiFePO4).

[0085] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 201 and a negative electrode active material layer 202 disposed on at least one surface of the negative electrode current collector.

[0086] In some embodiments, the negative electrode current collector 201 may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material layer 202 includes a negative electrode material, which is the negative electrode material of the first aspect described above or the negative electrode material prepared by the above preparation method.

[0087] The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.

[0088] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.

[0089] The following is a further description of the embodiments of the present application in multiple embodiments. The embodiments of the present application are not limited to the following specific embodiments. Within the scope of protection, appropriate changes can be made to the implementation.

[0090] Example 1 (1) Mix 7 parts of phenylenediamine and an appropriate amount of pure water, use 0.5 mol / L phosphoric acid solution to adjust the pH of the solution to 4, add 7 parts of 1 mol / L ammonium persulfate solution to adjust the oxidative environment of the mixed solution, continue stirring the reaction for 1 hour to cause a prepolymerization reaction, and obtain a prepolymerization solution.

[0091] (2) The prepolymer solution, 100 parts of graphite (average particle size of 17 μm) and an appropriate amount of pure water were stirred at a solid-liquid ratio of 1:3 to form a uniform mixed solution, and the liquid phase coating treatment was carried out for 12 hours under stirring. The polyphenylenediamine in the prepolymer solution was deposited and attached to the surface of the graphite particles. The mixed solution was then centrifuged, and the centrifuged product was moved to a drying oven at 120°C for 36 hours to obtain a precursor.

[0092] (3) In a nitrogen atmosphere, the precursor was heated to 1250°C for carbonization treatment for 4 hours, and then naturally cooled to obtain the negative electrode material.

[0093] Example 2 The difference from Example 1 is: (1) Mix 7 parts of aminostyrene and an appropriate amount of pure water, use 0.5 mol / L phosphoric acid solution to adjust the pH of the solution to 4, add 7 parts of 1 mol / L ammonium persulfate solution to adjust the oxidative environment of the mixed solution, and continue stirring the reaction for 1 hour to cause a prepolymerization reaction.

[0094] Example 3 The difference from Example 1 is: (1) Mix 7 parts of phenylenediamine and an appropriate amount of pure water, use 0.5 mol / L phosphoric acid solution to adjust the pH of the solution to 5, add 7 parts of 1 mol / L ammonium persulfate solution to adjust the oxidative environment of the mixed solution, and continue stirring the reaction for 1 hour to cause a prepolymerization reaction.

[0095] Example 4 The difference from Example 1 is: (1) Mix 7 parts of phenylenediamine and an appropriate amount of pure water, use 0.5 mol / L phosphoric acid solution to adjust the pH of the solution to 7, add 7 parts of 1 mol / L ammonium persulfate solution to adjust the oxidative environment of the mixed solution, and continue stirring the reaction for 1 hour to cause a prepolymerization reaction.

[0096] Example 5 The difference from Example 1 is: (1) Mix 7 parts of maleic anhydride and an appropriate amount of pure water, raise the solution temperature to 50°C and continue stirring for 2 hours to cause a prepolymerization reaction.

[0097] Example 6 The difference from Example 5 is: (1) Mix 7 parts of maleic anhydride and an appropriate amount of pure water, raise the solution temperature to 70°C and continue stirring for 2 hours to cause a prepolymerization reaction.

[0098] Example 7 The difference from Example 5 is: (1) Mix 7 parts of maleic anhydride and an appropriate amount of pure water, raise the solution temperature to 50°C and continue stirring for 4 hours to cause a prepolymerization reaction.

[0099] Example 8 The difference from Example 1 is: (1) Mix 7 parts of phenylenediamine and an appropriate amount of pure water, use 0.5 mol / L phosphoric acid solution to adjust the pH of the solution to 4, add 5 parts of 1 mol / L ammonium persulfate solution to adjust the oxidative environment of the mixed solution, and continue stirring the reaction for 1 hour to cause a prepolymerization reaction.

[0100] Example 9 The difference from Example 1 is: (1) Mix 7 parts of phenylenediamine and an appropriate amount of pure water, use 0.5 mol / L phosphoric acid solution to adjust the pH of the solution to 4, add 12 parts of 1 mol / L ammonium persulfate solution to adjust the oxidative environment of the mixed solution, and continue stirring the reaction for 1 hour to cause a prepolymerization reaction.

[0101] Example 10 The difference from Example 1 is: (2) The prepolymer solution, 100 parts of graphite (average particle size of 17 μm) and an appropriate amount of pure water were stirred at a solid-liquid ratio of 1:1.5 to form a uniform mixed solution. The liquid phase coating treatment was carried out for 12 hours under stirring to allow the diphenylamine in the mixed solution to undergo polymerization. The mixed solution was then centrifuged to separate the solid and liquid, and then moved to a drying oven for drying at 120°C for 36 hours to obtain a precursor.

[0102] Embodiment 11 The difference from Example 1 is: (1) Mix 4 parts of phenylenediamine and an appropriate amount of pure water, use 0.5 mol / L phosphoric acid solution to adjust the pH of the solution to 4, add 4 parts of 1 mol / L ammonium persulfate solution to adjust the oxidative environment of the mixed solution, and continue stirring the reaction for 1 hour to cause a prepolymerization reaction.

[0103] Example 12 The difference from Example 1 is: (1) Mix 25 parts of phenylenediamine and an appropriate amount of pure water, adjust the pH of the solution to 4 with 0.5 mol / L phosphoric acid solution, add 25 parts of 1 mol / L ammonium persulfate solution to adjust the oxidative environment of the mixed solution, and continue stirring the reaction for 1 hour to cause a prepolymerization reaction.

[0104] Example 13 The difference from Example 1 is: (3) In a nitrogen atmosphere, the precursor was heated to 1600°C for carbonization treatment for 4 hours, and then naturally cooled to obtain the negative electrode material.

[0105] Embodiment 14 The difference from Example 1 is: (3) In a nitrogen atmosphere, the precursor was heated to 2300°C for carbonization treatment for 4 hours, and then naturally cooled to obtain the negative electrode material.

[0106] Embodiment 15 The difference from Example 1 is: (2) The prepolymer solution, 100 parts of graphite (average particle size of 10 μm) and an appropriate amount of pure water were stirred at a solid-liquid ratio of 1:3 to form a uniform mixed solution. The liquid phase coating treatment was carried out for 12 hours under stirring to allow the diphenylamine in the mixed solution to undergo polymerization. The mixed solution was then centrifuged to separate the solid and liquid, and then moved to a drying oven for drying at 120°C for 36 hours to obtain a precursor.

[0107] (3) In a nitrogen atmosphere, the precursor was heated to 2300°C and kept at that temperature for 4 h, and then naturally cooled to obtain the negative electrode material.

[0108] Example 16 The difference from Example 1 is: (2) The prepolymer solution, 100 parts of graphite (average particle size of 6 μm) and an appropriate amount of pure water were stirred at a solid-liquid ratio of 1:3 to form a uniform mixed solution. The liquid phase coating treatment was carried out for 12 hours under stirring to allow the diphenylamine in the mixed solution to undergo polymerization. The mixed solution was then centrifuged to separate the solid and liquid, and then moved to a drying oven for drying at 120°C for 36 hours to obtain a precursor.

[0109] (3) In a nitrogen atmosphere, the precursor was heated to 2300°C and kept at that temperature for 4 h, and then naturally cooled to obtain the negative electrode material.

[0110] Embodiment 17 The difference from Example 1 is: (1) Mix 7 parts of phenylenediamine and an appropriate amount of pure water, use 0.5 mol / L phosphoric acid solution to adjust the pH of the solution to 4, add 7 parts of 1 mol / L ammonium persulfate solution to adjust the oxidative environment of the mixed solution, continue stirring the reaction for 3 hours to cause a prepolymerization reaction, and obtain a prepolymerization solution.

[0111] Comparative Example 1 The difference from Example 1 is: (2) The prepolymer solution, 100 parts of graphite (average particle size of 17 μm) and an appropriate amount of pure water were stirred at a solid-liquid ratio of 1:1.1 to form a uniform mixed solution. The stirring reaction was continued for 12 hours. The diphenylamine in the mixed solution was polymerized. The mixed solution was then centrifuged to separate the solid and liquid, and then moved to a drying oven for drying at 120°C for 36 hours to obtain a precursor.

[0112] Comparative Example 2 The difference from Example 1 is: (1) Mix 0.8 parts of phenylenediamine and an appropriate amount of pure water, adjust the pH of the mixture to 4 with 0.5 mol / L phosphoric acid solution, add 0.8 parts of 1 mol / L ammonium persulfate solution to adjust the oxidative environment of the mixture, and continue stirring the reaction for 1 hour to cause a prepolymerization reaction.

[0113] (2) The prepolymer solution, 100 parts of graphite (average particle size of 17 μm) and an appropriate amount of pure water were stirred at a solid-liquid ratio of 1:1.3 to form a uniform mixed solution. The stirring reaction was continued for 12 hours. The diphenylamine in the mixed solution was polymerized. The mixed solution was then centrifuged to separate the solid and liquid, and then moved to a drying oven for drying at 120°C for 36 hours to obtain a precursor.

[0114] Comparative Example 3 The difference from Example 1 is: (3) In a nitrogen atmosphere, the coating material precursor is heated to 700°C and maintained at 4°C, and then naturally cooled to obtain a highly structured disordered carbon-coated graphite material.

[0115] Comparative Example 4 The difference from Example 1 is: (1) Mix 7 parts of phenylenediamine and an appropriate amount of pure water, adjust the pH of the mixture to 10 with 0.5 mol / L phosphoric acid solution, add 7 parts of 1 mol / L ammonium persulfate solution to adjust the oxidative environment of the mixture, and continue stirring the reaction for 1 hour to cause a prepolymerization reaction.

[0116] Comparative Example 5 The difference from Example 1 is: (1) Mix 7 parts of phenylenediamine and an appropriate amount of pure water, use 0.5 mol / L phosphoric acid solution to adjust the pH of the solution to 4, add 7 parts of 1 mol / L ammonium persulfate solution to adjust the oxidative environment of the mixed solution, continue stirring the reaction for 6 hours to cause a prepolymerization reaction, and obtain a prepolymerization solution.

[0117] Comparative Example 6 The difference from Example 1 is: (1) Mix 7 parts of phenylenediamine and an appropriate amount of pure water, use 0.5 mol / L phosphoric acid solution to adjust the pH of the solution to 4, add 7 parts of 1 mol / L ammonium persulfate solution to adjust the oxidative environment of the mixed solution, and proceed to the next step without prepolymerization.

[0118] Comparative Example 7 The difference from Example 1 is: (2) The prepolymer solution, 100 parts of graphite (average particle size of 17 μm) and an appropriate amount of pure water were stirred at a solid-liquid ratio of 1:3 to form a uniform mixed solution, and the liquid phase coating treatment was carried out for 2 hours under stirring. The polyphenylenediamine in the prepolymer solution was deposited and attached to the surface of the graphite particles. The mixed solution was then centrifuged, and the centrifuged product was moved to a drying oven at 120°C for 36 hours to obtain a precursor.

[0119] Test Method (1) Test method for particle size distribution of negative electrode materials: The particle size distribution range of negative electrode materials was tested by Malvern 3000 laser particle size analyzer. Dispersant (ethanol, pure water and low-foaming surfactant) and the test sample were placed in a 50 mL beaker, and a certain amount of pure water was added. The sample was fully stirred with a glass rod to disperse the sample evenly. The equipment pump speed was set to 2400 r / min~2500 r / min and the frequency was 19.5 Hz for particle size test.

[0120] (2) Test method for the tap density of negative electrode materials: Place the negative electrode material in the sample chamber of the tap density meter, vibrate it 1000 times and record the sample volume at this time. The tap density can be calculated according to the mass-to-volume ratio.

[0121] (3) Test method for specific surface area of ​​negative electrode material: Use the precision micro-Gaobo DX400 to test the specific surface area of ​​the material. Put the sample into the sample tube, use the isothermal jacket on the sample tube, put the filling rod into the bubble tube, install the clamp ring and O-ring on the bubble tube, and then put the assembled sample bubble tube into the corresponding analysis station for testing. Under constant temperature and low temperature, after measuring the adsorption amount of gas on the solid surface at different relative pressures, the adsorption amount of the sample monolayer is obtained based on the Brown-Ett-Taylor adsorption theory and its formula (BET formula), thereby calculating the specific surface area of ​​the material.

[0122] (4) Oil absorption value test method of negative electrode material: The oil absorption value Q is tested using the ASAHI S-500 oil absorption value tester of ASAHISOUKEN of Japan. The oil absorption value Q is the amount of linseed oil added when the torque generated by the change in viscosity characteristics reaches 70% of the maximum torque, and the unit is mL / 100g.

[0123] (5) Test method for the surface morphology, cross section and coating of negative electrode material particles: Use HITACHI-S4800 scanning electron microscope to observe the microscopic morphology of the surface of negative electrode material. The steps are as follows: stick the conductive glue on the sample cup, evenly apply the sample on the conductive glue, use an ear-cleaning bulb to blow away the sample that is not firmly fixed, and put it into the scanning electron microscope room for testing. The test steps for the cross section and coating are as follows: first use the HITACHI-E3500 ion milling machine to polish the graphite particles, apply a small amount of carbon conductive glue on the edge of the sample stage, and evenly sprinkle the graphite sample, press lightly with a glass sheet, wait for 2 minutes for the conductive glue to dry, and blow away the excess sample with an ear-cleaning bulb. Place the sample stage on the sample holder, adjust the sample position, and after completion, adjust the airflow to the maximum ion beam current, set the polishing time for sample processing. After completion, use the HITACHI-S4800 scanning electron microscope to observe the cross section and coating of the surface of the negative electrode material.

[0124] (6) Raman test method for negative electrode materials: Use HORIBA-XPLORA laser confocal Raman spectrometer to test Raman scattering spectrum, laser wavelength 532 nm. Take 30 points on the surface of negative electrode material particles for data collection, and then perform peak fitting on the scattering spectrum obtained at each point to obtain the peak at 1300cm -1 ~1350cm -1 The peak area of ​​the characteristic peak D in the range of 1500 cm -1 ~1580cm -1 The peak area ratio of the G characteristic peak within the range is I D / I G , I D / I G The average value is A. After the negative electrode material particles are cut, the particles are cut using a HITACHI-E3500 ion milling machine, and the cut surface area is tested. Ten points are randomly selected in the particle cut surface area for Raman spectrum scanning, and the Raman spectrum at 1300 cm -1 ~1350cm -1 The peak area of ​​the characteristic peak D in the range of 1500 cm -1 ~1580cm -1 The peak area ratio of the G characteristic peak within the range is I D / I G , I D / I G The average value is B.

[0125] (7) Method for measuring polymer degree of polymerization: Use a gel permeation chromatography instrument to test the degree of polymerization of the polymer in the prepolymer solution. Gel permeation chromatography (GPC), also known as size exclusion chromatography, is a liquid chromatography method that uses a solvent as a mobile phase and flows through a porous filler (such as porous silica gel or porous resin) as a separation medium. As the solvent is eluted, molecules of different sizes are separated, with larger molecules eluted first and smaller molecules eluted later. The molecular weight of the polymer and its distribution are obtained by analysis, and the molecular weight of the polymer / molecular monomer molecular weight is the degree of polymerization.

[0126] (8) Atomic force microscope test method: Use an atomic force microscope (AFM) to test the surface flatness of graphite materials. Fix one end of a micro cantilever that is extremely sensitive to weak forces and have a tiny needle tip at the other end, so that it is gently in contact with the sample surface. Due to the extremely weak repulsive force between the atoms at the tip of the needle tip and the atoms on the sample surface, the cantilever will deflect slightly. By detecting the deflection amount and using feedback to control the constant repulsive force, the position change of the micro cantilever corresponding to each point can be obtained, thereby obtaining an image of the sample surface morphology. Randomly select 1μm from the image. 1μm test area, the arithmetic mean of the absolute value of the height deviation relative to the reference surface in the test area is S nm, 15nm≤S≤60nm, where S= , n≥5, Z is the height deviation value (i.e., the ordinate value) of any test point in the test area relative to the reference plane. This application uses the tapping mode: the probe maintains a fixed frequency vibration on the Z axis, and contacts the sample when the vibration reaches the bottom, which causes little damage to the sample and has a higher resolution. In this application, the reference plane of the atomic force microscope is an equipotential plane determined by detecting and analyzing the weak force between the needle tip and the atoms on the sample surface, and is the plane corresponding to the average value of the height values ​​of all test points.

[0127] (9) Electrochemical performance test method: The negative electrode materials prepared in the examples and comparative examples were dissolved in deionized water at a mass ratio of 96.5:1.5:1 for the negative electrode material, carboxymethyl cellulose and styrene-butadiene rubber, respectively, and the solid content was controlled to be 50%. The negative electrode sheets were coated on copper foil current collectors and vacuum dried to obtain negative electrode sheets. Metal lithium sheets were used as counter electrodes and assembled into button cells in a glove box filled with argon. The charge and discharge tests were performed at a current density of 0.1C with a charge and discharge interval of 0.01-1.5V. The first reversible specific capacity, first cycle charge capacity and first cycle discharge capacity were obtained by cyclic charge and discharge. First coulomb efficiency = first cycle discharge capacity / first cycle charge capacity.

[0128] After completing the above tests, the charging current density was set to 0.2C, and the discharge lithium insertion tests were performed at current densities of 0.2C, 0.5C, 1C, and 2C, respectively. The 2C / 0.2C rate performance = 0.2C discharge lithium insertion capacity / 2C discharge lithium insertion capacity.

[0129] The preparation process parameters and corresponding test results of Examples 1 to 17 (abbreviated as S1 to S17) and Comparative Examples 1 to 7 (abbreviated as D1 to D7) prepared in the present application are shown in Tables 1 and 2 below.

[0130] Table 1. Preparation process parameters of negative electrode materials Table 2. Performance parameters of negative electrode materials and batteries prepared in various examples and comparative examples The negative electrode material prepared by the preparation method provided in the present application is prepared by prepolymerizing a coating agent having an active group, and the degree of polymerization of the polymer in the obtained prepolymer solution is in the range of 3-30, and the polymer is mainly an oligomer with a small molecular chain, which can be evenly dispersed in the prepolymer solution. Then, graphite is added to the prepolymer solution for liquid phase coating. During the coating process, the polymer evenly dispersed in the prepolymer solution can be deposited and attached to the surface of the graphite particles to form a uniform polymer coating layer; at the same time, the solid-liquid ratio of graphite to the prepolymer solution is controlled to be 1: (1.3-3.5), and the mass ratio of graphite to the coating agent is 100: (4-30), so that the thickness of the polymer coating layer evenly attached to the graphite surface is within a suitable range, while improving the capacity of the negative electrode material, the lithium ion interface transmission efficiency of the negative electrode material is improved.

[0131] Finally, through carbonization treatment, the polymer coating layer can be fully carbonized to form a carbon layer. The carbon material in the carbon layer has a high degree of disorder. The difference in the Raman ratio between the surface of the negative electrode material particles and the inside of the particles can also be within a suitable range. In addition, the flatness of the coating layer on the surface of the negative electrode material can also be within a suitable range. The above preparation method not only ensures the regularity of the graphite structure inside the negative electrode material particles, but also the connection interface between the graphite and the carbon layer can have better transmission power, and improves the wettability of the contact interface between the surface of the negative electrode material and the electrolyte. The negative electrode material prepared by the preparation method of the present application has AB greater than 1.22 and less than or equal to 2.10, indicating that the Raman ratio A of the carbon layer and the Raman value B (graphite) of the cross section of the negative electrode material are both in a reasonable range. At this time, the negative electrode material can have both excellent lithium ion transmission power performance and high capacity. S is in the range of 15nm~60nm, indicating that the surface coating layer of the material is evenly distributed on the surface of the graphite particles. At the same time, the flatness of the coating layer is also in a suitable range, which is conducive to electrolyte infiltration and interface impedance reduction. The graphite negative electrode material provided by this patent not only ensures the regularity of the graphite structure inside the particles, so that the interface between the graphite and the carbon layer can have better transmission power, but also improves the wettability of the contact interface between the surface of the negative electrode material and the electrolyte. The provided graphite negative electrode material can have excellent lithium ion transmission power performance, capacity, first coulomb efficiency and cycle performance.

[0132] Figure 3a and Figure 3b They are electron microscope images of the negative electrode material prepared in Example 1 of the present application at different magnifications; Figure 3a As shown in Figure 1, the carbon material in the carbon layer is evenly distributed on the surface of the graphite particles in a moss-like manner. Figure 3b As shown, the negative electrode material is distributed in potato-like particles, and there are almost no agglomerates of highly disordered carbon materials between the negative electrode material particles, indicating that the surface of the graphite material obtained by the preparation method of the present application is uniformly coated with highly disordered carbon materials. Figure 3c As shown, when the negative electrode material is cut open, moss-like highly disordered carbon material can also be observed on the surface of the exposed graphite sheet inside, which has the same morphology as the outer surface of the negative electrode material ( Figure 3a ), indicating that the preparation method provided in the present application can achieve uniform coating of highly disordered carbon materials outside the graphite particles. Figure 4a and Figure 4b They are the Raman spectra of the graphite negative electrode material and the cross section prepared in Example 1 of the present application. Combined with the data in Table 2, it can be found that the Raman ratio of the graphite material is 2.46, the Raman ratio of the cross section is 0.55, and the corresponding AB value is 1.91, which is in the range of 1.22~2.10. Figure 5 This is an atomic force microscope image of the graphite negative electrode material prepared in Example 1, and the corresponding S value is 23.6nm. The capacity, first efficiency and rate performance of the negative electrode material prepared in Example 1 are significantly improved.

[0133] According to the test data of Examples 1 to 2 and Example 5, the A value and AB value of the negative electrode material prepared by using different coating agents with active groups do not change much. At the same time, the S value of the negative electrode material is in the range of 15nm to 60nm, and the specific capacity, first coulombic efficiency and rate performance of the negative electrode material are good.

[0134] According to the test data of Example 1 and Examples 3 to 4, as the pH value increases, the A value of the prepared negative electrode material gradually decreases, the corresponding AB value also gradually decreases, and the S value also gradually decreases, indicating that the pH will affect the degree of polymerization of the polymer in the prepolymerization solution, thereby slightly reducing the disorder of the carbon material in the carbon layer, slightly increasing the surface flatness of the material, decreasing the capacity and first coulombic efficiency of the negative electrode material, and the rate performance does not change much.

[0135] According to the test data of Examples 5 to 7, when the coating agent is a coating agent having a carbon-carbon double bond, as the prepolymerization temperature increases, the A value of the prepared negative electrode material decreases; as the insulation time increases, the A value of the prepared negative electrode material also decreases; this is because the prepolymerization temperature and insulation time will affect the polymerization degree of the polymer formed by polymerization in the prepolymerization solution, the growth of the polymer molecular chain, and then affect the degree of disorder of the carbon layer on the surface of the negative electrode material. Within the prepolymerization temperature range and insulation time range of the present application, it is helpful to improve the capacity and the first coulombic efficiency of the negative electrode material.

[0136] According to the test data of Example 1 and Examples 8 and 9, as the amount of redox agent added increases, the degree of polymerization of the polymer in the prepolymerization solution gradually increases, the degree of disorder of the polymer deposited on the surface of the graphite particles gradually decreases, the A value of the negative electrode material prepared after carbonization also decreases, AB also decreases, and S also gradually decreases.

[0137] According to the test data of Example 1 and Example 10, during the stirring reaction of graphite and prepolymer solution, regulating the solid-liquid ratio in a suitable range can control the concentration of polymer molecules in the prepolymer solution per unit volume. As the concentration decreases, the deposition uniformity of polymer molecules on graphite particles decreases. As the solid-liquid ratio decreases, the A value of the negative electrode material gradually decreases, AB also decreases, and the S value increases significantly.

[0138] According to the test data of Examples 1 and 11-12, as the mass ratio of the coating agent to graphite increases, the amount of the coating agent added gradually increases, the thickness of the polymer coating layer deposited on the graphite surface increases, the A value of the obtained negative electrode material gradually increases, the corresponding AB also gradually increases, and the S value significantly decreases.

[0139] According to the test data of Examples 1 and 13-14, as the carbonization temperature increases, the disorder of the polymer carbonization layer deposited on the graphite surface gradually decreases, the A value of the obtained negative electrode material gradually decreases, the corresponding AB also gradually decreases, and the S value does not change much.

[0140] According to the test data of Examples 14 to 16, as the particle size of the raw material used changes, the thickness of the polymer layer deposited on the graphite surface gradually increases, the thickness of the corresponding coating layer also gradually increases, the A value and the corresponding AB of the carbonized material also gradually increase, and the S value does not change much. This shows that the preparation method of the present application is suitable for the preparation of graphite materials with different particle sizes and high surface disorder characteristics.

[0141] According to the test data of Example 1 and Example 17, as the prepolymerization time increases, the degree of polymerization of the polymer in the prepolymerization solution increases, the disorder of the corresponding polymer carbonization layer deposited on the graphite surface decreases, the A value of the obtained negative electrode material gradually decreases, the corresponding AB also gradually decreases, and the S value decreases.

[0142] Compared with Example 1, during the preparation process of Comparative Example 1, the solid-liquid ratio of graphite and prepolymer solution is too high, the deposition reaction of the polymer in the prepolymer solution on the graphite particles is uneven, the polymer exhibits self-nucleation growth and agglomeration phenomena, the Raman value of the prepared negative electrode material is A>3.00, AB>2.10, S>60.0nm, the specific surface area corresponding to the negative electrode material is relatively high, and the first coulomb efficiency and rate are significantly reduced.

[0143] Compared with Example 1, in the preparation process of Comparative Example 2, the amount of coating agent added is too low, the polymer concentration in the prepolymerization solution is also reduced, the polymer is difficult to deposit on the graphite particles to form a uniform coating layer, the Raman value of the prepared negative electrode material is A<1.70, AB<1.22, S>60.0nm, the specific surface area of ​​the negative electrode material is increased, and the capacity, first efficiency and rate of the negative electrode material are also reduced.

[0144] Compared with Example 1, during the preparation process of Comparative Example 3, the carbonization temperature is too low, the disorder degree of the carbon layer coating the outside of the graphite particles is relatively high, and the defects inside the graphite particles also increase synchronously. The Raman value of the prepared high-structure disordered carbon-coated graphite material is A>3.00, but AB is in the range of 1.22~2.10, and the S value is slightly higher than that of Example 1. The specific surface area of ​​the negative electrode material is relatively high, and the first efficiency is reduced.

[0145] Compared with Example 1, during the preparation process of Comparative Example 4, the pH value when the prepolymer solution is formed is relatively high, and the degree of polymerization of the polymer in the prepolymer solution increases, resulting in a decrease in the disorder of the carbon layer coated on the outside of the graphite particles. The Raman value of the prepared negative electrode material is A<1.70, but AB is in the range of 1.22~2.10, S<15nm, the specific surface area of ​​the negative electrode material is relatively high, and the first efficiency and rate are reduced.

[0146] Compared with Example 1, in the preparation process of Comparative Example 5, the prepolymerization stirring time was controlled too long, the polymerization degree of the polymer in the prepolymerization solution increased, resulting in a decrease in the disorder of the carbon layer coated on the outside of the graphite particles. The Raman value of the prepared negative electrode material was A<1.70, AB<1.22, and the S value was in the range of 15nm~60nm, and the capacity, first efficiency and rate of the negative electrode material were reduced.

[0147] Compared with Example 1, Comparative Example 6 did not undergo pre-polymerization treatment during the preparation process, resulting in the coating agent not being completely deposited on the surface of the graphite particles. The coating layer thickness was reduced under the same coating amount, and the Raman value of the prepared negative electrode material was A<1.70, AB<1.22, S>60.0nm, the specific surface area of ​​the negative electrode material was increased, the side reaction of the negative electrode material with the electrolyte was intensified, and the capacity, first effect and rate of the negative electrode material were reduced.

[0148] Compared with Example 1, in the preparation process of Comparative Example 7, the stirring time after adding graphite powder was too short, resulting in the coating agent not being evenly distributed on the surface of the graphite particles, the Raman value of the prepared negative electrode material was A>3.00, AB>2.10, S>60.0nm, the specific surface area of ​​the negative electrode material was increased, the side reaction of the negative electrode material and the electrolyte was intensified, and the capacity, first efficiency and rate of the negative electrode material were reduced.

[0149] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.

Claims

1. A negative electrode material for a lithium ion battery, characterized in that: The negative electrode material includes graphite and a carbon layer located on at least a portion of the surface of the graphite; Raman spectroscopy was used to test the particle surface and particle cross-section of the negative electrode material. -1 ~1350cm -1 The peak area of ​​the characteristic peak D in the range of 1500 cm -1 ~1580cm -1 The peak area ratio of the G characteristic peak within the range is I D / I G , the I on the surface of the particles of the negative electrode material is measured D / I G The ratio is A, the I D / I G The ratio is B, 1.22<AB≤2.10; The particle surface of the negative electrode material was tested by atomic force microscopy. A 1 μm particle was randomly selected from the particle surface of the negative electrode material. 1μm test area, the arithmetic mean of the absolute value of the height deviation relative to the reference surface in the test area is S nm, 15nm≤S≤60nm, where S= , n≥5, Z is the height deviation value of any test point in the test area relative to the reference surface.

2. The negative electrode material of a lithium ion battery according to claim 1, characterized in that: 1.70≤A≤3.00, 0.4≤B≤0.

8.

3. The negative electrode material of the lithium ion battery according to claim 1, characterized in that: The negative electrode material satisfies at least one of the following characteristics: 1) The graphite includes at least one of artificial graphite, natural graphite and microcrystalline graphite; 2) The fixed carbon content of the graphite is ≥ 95%.

4. The negative electrode material of the lithium ion battery according to claim 1, characterized in that: The thickness of the carbon layer is 15 nm to 250 nm; and / or the carbon layer comprises amorphous carbon.

5. The negative electrode material of the lithium ion battery according to claim 1, characterized in that: The negative electrode material satisfies at least one of the following characteristics: (1) The median particle size of the negative electrode material is 4 μm to 25 μm; (2) The specific surface area of ​​the negative electrode material is ≤ 6m 2 / g; (3) The tap density of the negative electrode material is 0.75 g / cm 3 ~1.3g / cm 3 .

6. The negative electrode material of the lithium ion battery according to claim 1, characterized in that: The oil absorption value of the negative electrode material is 38 mL / 100g~48 mL / 100g.

7. A method for preparing a negative electrode material for a lithium ion battery according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: Dispersing a coating agent having an active group and a reaction regulator in an aqueous solution, and performing a prepolymerization reaction to obtain a prepolymerization solution, wherein the degree of polymerization of the polymer in the prepolymerization solution is 3 to 30; Adding graphite to the prepolymer solution for liquid phase coating, and performing solid-liquid separation to obtain a precursor, wherein the solid-liquid ratio of the graphite to the prepolymer solution is 1:(1.3-3.5), and the mass ratio of the graphite to the coating agent is 100:(4-30); The precursor is carbonized to obtain a negative electrode material.

8. The method for preparing the negative electrode material of a lithium ion battery according to claim 7, characterized in that: The method satisfies at least one of the following characteristics: (1) The active group includes at least one of a carbon-carbon double bond, a carboxyl group, a hydroxyl group and an amine group; (2) The reaction regulator includes at least one of a redox agent and a pH regulator; (3) The reaction regulator includes a redox agent, and the mass ratio of the redox agent to the coating agent is 1:(0.7-2.0); (4) The prepolymerization reaction time is controlled to be 1 h to 4 h; (5) The liquid phase coating time is 4h to 24h; (6) The coating agent having an active group includes at least one of styrene, fluorostyrene, bromostyrene, aminostyrene, styrenic acid, phenylpropionic acid, aniline, phenylenediamine, acrylic acid, methyl acrylate, ethyl acrylate, phenyl acrylate, benzyl acrylate, acrylamide, methacrylamide, ethylacrylamide, phenylacrylamide, maleic acid, maleic anhydride, maleic acid diamine, citric acid, mesaconic acid, itaconic acid, itaconic anhydride, aminosulfonic acid, ammonium aminosulfonate, benzoic acid, ammonium benzoate, and p-fluorobenzoic acid.

9. The method for preparing the negative electrode material of a lithium ion battery according to claim 7, characterized in that: The method satisfies at least one of the following characteristics: (1) The temperature of the carbonization treatment is 1000°C to 2300°C; (2) The heat preservation time of the carbonization treatment is 0.5h~6h, (3) The carbonization treatment is carried out under a protective atmosphere.

10. A lithium ion battery, characterized in that: The lithium ion battery comprises the negative electrode material of the lithium ion battery according to any one of claims 1 to 6 or the negative electrode material of the lithium ion battery prepared by the preparation method according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Composite graphite particles and lithium secondary battery using the same

    CN102341346A

  • Negative electrode material, and electrochemical device and electronic apparatus comprising same

    CN113066977A

  • Battery

    CN116111074A

  • Negative electrode material, preparation method thereof and lithium ion battery

    CN116979056A

  • Non-aqueous electrolyte solution secondary battery and its negative electrode material

    US20040126662A1